Control of manufacturing systems with downstream batch processors - Cheng, Tajan John Benedict (2008)
Batch processors can concurrently process more than one batch and are regularly used in the semiconductor manufacturing industry, particularly in the wafer fabrication stage. The reentrant nature of the wafer fab and the incompatibility of jobs from different job families, combined with the typically long processing times of the batch processor, make the control of batch processors an interesting problem with important implications. Current literature has predominantly assumed that the batch processor exists in isolation, and treats the job arrival pattern it receives as a problem constraint. We propose to control the job arrival pattern of the batch processors by controlling the processor immediately upstream of the batch processor, such that the performance of the over-all system is improved.